2010
DOI: 10.1124/mol.110.068494
|View full text |Cite
|
Sign up to set email alerts
|

Design, Preparation, and Characterization of High-Activity Mutants of Human Butyrylcholinesterase Specific for Detoxification of Cocaine

Abstract: Cocaine is a widely abused drug without a U.S. Food and Drug Administration-approved medication. There is a recognized, promising anticocaine medication to accelerate cocaine metabolism, producing biologically inactive metabolites via a route similar to the primary cocaine-metabolizing pathway [i.e., cocaine hydrolysis catalyzed by butyrylcholinesterase (BChE) in plasma]. An ideal, therapeutically valuable mutant of human BChE should have not only a significantly improved catalytic activity against (Ϫ)-cocaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
104
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 39 publications
2
104
0
1
Order By: Relevance
“…In an attempt to improve upon BChE's catalytic efficiency, Zhan and colleagues have used site-directed mutagenesis to create mutant BChEs capable of hydrolyzing cocaine B450-2000 times more efficiently than native BChE (Pan et al, 2005;Zheng et al, 2008). These mutant BChEs have shown promising results when evaluated in rodents, effectively reducing the cardiovascular, lethal, and response-reinstating effects of cocaine (Brimijoin et al, 2008;Xue et al, 2010;Zheng et al, 2008). In addition, an albumin-fused mutant BChE (Albu-CocH) has been shown to decrease progressive ratio responding for cocaine (Carroll et al, 2011), suggesting that it is also capable of reducing the reinforcing effectiveness of cocaine.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to improve upon BChE's catalytic efficiency, Zhan and colleagues have used site-directed mutagenesis to create mutant BChEs capable of hydrolyzing cocaine B450-2000 times more efficiently than native BChE (Pan et al, 2005;Zheng et al, 2008). These mutant BChEs have shown promising results when evaluated in rodents, effectively reducing the cardiovascular, lethal, and response-reinstating effects of cocaine (Brimijoin et al, 2008;Xue et al, 2010;Zheng et al, 2008). In addition, an albumin-fused mutant BChE (Albu-CocH) has been shown to decrease progressive ratio responding for cocaine (Carroll et al, 2011), suggesting that it is also capable of reducing the reinforcing effectiveness of cocaine.…”
Section: Introductionmentioning
confidence: 99%
“…Through a series of site-directed mutagenesis studies, Zhan and colleagues identified mutant BChEs capable of hydrolyzing cocaine approximately 450 to 2000 times faster than native BChE (Pan et al, 2005;Zheng et al, 2008). In rats and mice, these mutant BChEs effectively reduced the cardiovascular, lethal, and abuse-related effects of cocaine (Brimijoin et al, 2008;Zheng et al, 2008;Carroll et al, 2011;Xue et al, 2011), suggesting that such enzymes may provide a viable strategy for treating cocaine toxicity and abuse in humans.…”
Section: Introductionmentioning
confidence: 99%
“…A biological t 1/2 of 43-77 h in humans might be adequate for a twice-weekly therapy, depending on the dose of the enzyme used. In addition, our more recently designed and identified CocHs (12)(13)(14) are significantly more active than TV-1380 against (-)-cocaine. Further engineering a more active CocH with a biological t 1/2 longer than that of TV-1380 is highly desired.…”
mentioning
confidence: 92%
“…Through structure-and mechanism-based computational modeling and simulation, we have successfully designed and identified human BChE mutants, recognized as true cocaine hydrolases (CocHs) in the literature (9) when they have at least 1,000-fold improved catalytic efficiency against (-)-cocaine compared with wild-type human BChE (11)(12)(13)(14). The first of our designed CocHs, known as "CocH1" (the A199S/S287G/A328W/Y332G mutant of human BChE) (11,15), truncated after amino acid 529, was fused with human serum albumin (HSA) to prolong the biological t 1/2 (9).…”
mentioning
confidence: 99%